Hubungan Umur, Tingkat Pendidikan dan Pendapatan dengan Kepuasan Pengunjung Wisata Pantai Membuku di Kabupaten Buton Utara - Yusdin; Budiyanto; Rosmawati (Universitas Halu Oleo, 2021)
One of the natural attractions that is frequently visited by mostly local tourists in North Buton Regency is Membuku Beach. Tourists who come to the beach consist of various backgrounds ranging from age, education level and income which are expected to affect tourist satisfaction in this beach. The purpose of this study was to determine the relationship between age, education level and income with visitor satisfaction levels. This research was conducted during the period March to April 2020. The population in this study were all visitors to the tourist attraction, while the sample was selected using the accidental sampling method as many as 50 tourists. Analysis of data using Pearson correlation analysis using Microsoft Excel 2007 application. The results of the analysis show that the variable age with the satisfaction level of visitors to the Membuku beach tourism has a correlation coefficient value of 0.98, meaning that the age variable with the visitor satisfaction level has a very strong relationship because of the correlation coefficient value. close to number one, and vice versa if the value of the correlation coefficient is close to zero, it means that the two variables are very weak. The correlation coefficient value of the education level variable with the satisfaction level of visitors to the Membuku Beach tour is 0.99, which means that the education level variable with the visitor satisfaction level has a very strong relationship, while the relationship between the income variable and the satisfaction level of the visitors to Membuku Beach tourism has a correlation coefficient value of 0.60. This means that the income variable and the level of visitor satisfaction has a strong relationship. This means that the higher the tourist income, the higher the correlation coefficient value. Therefore, the manager must improve the quality of the tourist attraction facilities so that they are sustainable and can get a better assessment from tourists who visited Membuku Beach in the future.